Counseling in Indonesian Education: Systematic Literature Review - Muttaqin, Mohammad Izdiyan; Sofiandari, Hesty (Universitas Islam Indonesia, 2024)
Counselling is an important element in education that functions to help students develop mental, emotional, learning skills, and future career development. This article aims to discover the concept of counselling guidance in Indonesian education. Systematic Literature Review is conducted to find references relevant to the research theme. Of the 100 articles that were successfully accessed through the Open Knowledge Maps data bank, nine articles were selected and analysed manually. The selected articles were divided into three groups: a cluster of religion and culture-based counselling, a cluster of procunialism and management in counselling, and a cluster of alternative methods in counselling. The results of this study show that counselling guidance in Indonesian education has strong relationship with cultural and religious values in which counselling guidance can be done by friends, upperclassmen, parents or teachers, and can be done with a variety of different methods. This article provides an overview of the development of the literature on counselling guidance in education in Indonesia in recent times.